Debaters’ Critical Thinking Skills In Reading Text - Firman, Edi (Lembaga Penelitian dan Pendidikan Mandala, 2023)
This research aimed at finding out the measurement of the level of E2DC debater’s critical thinking skill in reading newspaper and the strategy that used. There were many important things as debaters that were: make argumentation well, practice critical thinking and good public speaking as native speaker. Not only that but also you will have confidently in the classroom when you presentation and felt easier than other students. In providing evidence the debater should have good background of knowledge because that was the way to increase debaters’ critical thinking. The members of this community were trained to becoming debaters and being able to make an argumentation well and have critical thinking skills with kind of issue. The researcher identified several problems in Debaters’ critical thinking skills. In other words, a debater must have critical skills to understand the main idea from the text and can make inference by their own words. Not only that but also, they must be able to make it different between the fact, opinion and non-fact. The result of observation section. First debater was Excellent as the OG (Opening Government), the second debater was Average as the OO (Opening opposition), the third debater was Good as the CG (Closing Government) and the last or the fourth debater was Below Average as the CO (Closing Opposition). From all the percentage shows that, the percentage of using Cognitive Domain in reading skills from the four debaters is higher than Incorporating Critical Thinking.